Additional Intermediate Tension Coefficients in Cylindrical Liquid Storage Tanks under Hinged Base Condition - Shirish Vichare, Anand Daftardar (International Journal of Scientific Research and Management (IJSRM), 2017)
Hoop tension coefficients for analysis of cylindrical liquid storage tanks are available in codes of practice of various countries and also in Portland Cement Association (PCA). Hoop tension coefficients values are dependent on the dimension parameters, ranging from 0.4 to 16. Since these coefficients are available in irregular intervals with the assumption that the intermediate coefficients can be calculated by interpolation. This paper shows graphically and with the table providing in the appendix by solving the fourth order differential equation that the hoop tension coefficient values, calculated from interpolation is not accurate with the increasing from 0.4 to 16. Availability of these intermediate hoop tension coefficients for from 0.4 to 16 with interval of 0.1 will not only facilitate analysis and design process for variety of tank dimensions with better accuracy but also provides ease to the practicing engineers.